Automatic system of choosing of fixtures - Rodić, Milorad (Journal of Production Engineering, 1985)
In this article, the results of the research in the field of automatic fixture selection system are presented. The selection of fixtures is based on the developed system of marking, especially classification. On the basis of the developed classification system it is possible to obtain information about the rental solutions of fixtures (working construction, typical construction, essential construction) from bank data.